Astrophysical Properties of the Sirius Binary System Modeled with MESA - Momin Y. Khan; Barbara G. Castanheira (The Astrophysical Journal)
Sirius is the brightest star in the night sky and, despite its proximity, this binary system still imposes intriguing questions about its current characteristics and past evolution. H. E. Bond et al. published decades of astronometric measurements of the Sirius system, determining the dynamical masses for Sirius A and B, and the orbital period. We have used these determinations, combined with photometric determinations for luminosity and spectroscopic determinations of effective temperature ( T _eff ) and metallicity, to model the evolution of the Sirius system using Modules for Experiments in Stellar Astrophysics. We have constructed a model grid calculated especially for this system and were able to obtain, for Sirius B, a progenitor mass of 6.0 ± 0.6 M _⊙ , yielding a white dwarf mass of 1.015 ± 0.189 M _⊙ . Our best determination for the age of the system is 203.6 ± 45 Myr with a metallicity of 0.0124. We have compared our best-fit models with the ones computed using TYCHO, YREC, and PARSEC, establishing external uncertainties. Our results are consistent with the observations and support a noninteracting past.